If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9ln(6x) = 45 Remove parenthesis around (6x) 9ln * 6x = 45 Reorder the terms for easier multiplication: 9 * 6ln * x = 45 Multiply 9 * 6 54ln * x = 45 Multiply ln * x 54lnx = 45 Solving 54lnx = 45 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Divide each side by '54nx'. l = 0.8333333333n-1x-1 Simplifying l = 0.8333333333n-1x-1
| 2+x=3x-14 | | ln(x^4)=8 | | 10=12-x | | 4x-1=14-121 | | lnx^4=8 | | -6x+5=-91+2x | | 4x-1=14-21 | | (2-v)(4v+3)=0 | | 4x+34=11-29 | | x^2-(2+2)*2=10 | | 7-7x=7x-91 | | 4x+5=-51+10x | | 3(2-x)-1=4(3-x) | | x(3x-5)(x+4)(x-7)=0 | | -6(6x+5)=-246 | | 4x+5=51-10x | | y=-2(x-4)2nd+3 | | 330*1=-16x | | k^2+6k+8=0 | | 4t-2(3-t)-3(t-7)= | | q^2+2q-48=0 | | 118-4=5x+10 | | Jx+ky=m | | y=-2(x-4)2+3 | | 4.5x-3.4=2.1x-.4 | | 5x^2+40x+35=0 | | -5n(4n-1)=0 | | -6-6x=12-10x | | 4x^2=36x-72 | | 3x+9=10+3x+1 | | X^4-12x^2+35=0 | | 8x+27=4x+87 |